Pengaruh Faktor Kerawanan Pangan Dan Lingkungan Terhadap Stunting - Aris Widiyanto; Joko Tri Atmojo; Aquartuti Tri Darmayanti (Poltekkes Kemenkes Surakarta, 2019)
Background: Globally, it is estimated that one in five children will fail to grow or be known as stunting in 2020. In Indonesia based on Nutritional Status Monitoring (PSG) data for the past three years. The prevalence of short-term toddlers has increased from 2016 to 27.5% to 29.6% in 2017. Method: The interaction between environment and nutrition, especially food insecurity presents interesting dynamics that can be studied further. In this review, the authors are interested in providing scientific evidence-based information about the effects of food and environmental vulnerability factors on the incidence of stunting. Search for published articles is done through databases: PubMed, EMBASE, Scopus, CINAHL (EBSCO), the official website of national health organizations, online libraries, and the UNICEF library from February 10 to March 25, 201. Result: Stunting AND Risk Factors, Factors affecting stunting, Stunting AND food insecure, stunting AND environment factors, Stunting AND Indonesia. Inclusion criteria were systematic reviews, clinical reviews, cohort studies, cross-sectional studies, clinical studies, health reports, and program guidelines. Conclusion: Factors influencing stunting including: food insecurity increases the risk of stunting (OR = 1.17 95% CI: 1.09-1.25) and less weight (OR = 1.17 95% CI: 1.01-1.36). lack of sanitation, flooring type and mycotoxin exposure in the form of AF-alb.